2021
DOI: 10.1016/j.funbio.2019.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxins occurrence and fungal populations in different types of silages for dairy cows in Spain

Abstract: Està subjecte a una llicència de Reconeixement-NoComercial-SenseObraDerivada 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 41 publications
2
20
0
2
Order By: Relevance
“…The presence of Cladosporium indicated that inoculation of LAB showed a limited effect on the stability of silage at the final stage of ensiling. Genera of Rhizopus occurred rarely in silages ( Rodríguez-Blanco et al, 2021 ). It was first reported that Buckleyzyma salicina distributed in timothy silage.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of Cladosporium indicated that inoculation of LAB showed a limited effect on the stability of silage at the final stage of ensiling. Genera of Rhizopus occurred rarely in silages ( Rodríguez-Blanco et al, 2021 ). It was first reported that Buckleyzyma salicina distributed in timothy silage.…”
Section: Discussionmentioning
confidence: 99%
“…FBs production is stimulated by certain environmental conditions: maximum accumulation of FBs by F . verticillioides in maize usually occurs between 20 and 25°C, and favourable a w levels are established between 0.95 and 0.99 (Marín et al, 2004; Mogensen et al, 2009; Yu et al, 2021), which are situations that can be commonly found during maize silage (Rodríguez‐Blanco et al, 2021). It is under these advantageous conditions that the antifungals should present outstanding FBs diminishing effects.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the mitigation efforts, exposure of crops to mycotoxins is indeed inevitable and decontamination is very difficult [ 3 , 4 ]. Even though numerous studies concerning the effect of mycotoxins are reported in the specific literature, the contamination of cereals with fusariotoxins, the impact on animal health and the economic losses they imply [ 5 , 6 , 7 ], the transmission of fusariotoxins into the target organism and the potential existence of toxic components in meat and dairy products remain unknown and need further investigations [ 8 ].…”
Section: Introductionmentioning
confidence: 99%